Age Estimation in Callow Adolescents and Young Adults Using Volumetric Analysis of Mandibular Third Molars: A CBCT Study - Sairam Vankadara; Kavali Laxmi Swetha (Wolters Kluwer Medknow Publications, 2024)
Background: Age estimation is a preliminary assessment that aids in medico legal assessments and legal proceedings. Teeth development or mineralization is the efficacious for assessment of age and Cone Beam Computed Tomography (CBCT) scans, an advanced imaging modality can be used for the same. Aim: To investigate the association between chronological age and the surface area of the maturing mandibular 3rd molar apices using CBCT scans and in addition, to formulate a regression equation for estimating age. Material and Methods: This study included 120 CBCT scans of different age groups ranging from 13 to 24 years consisting of 66 males and 54 females. MIMICS and 3-MATIC software assist' were used in calculating root apices surface areas and using the obtained surface area, a regression equation is formulated for age estimation in Andhra Pradesh population. Results: A positive correlation was noted between the surface area of developing molar roots and age where Pearson R value = 0.910 and independent sample "t" test showed significance at <.001 (P value < 0.05 significant). Conclusion: The study showed a significant reduction in the surface area of root apices as chronological age progressed. Analysis of the 3D models led to the estimation of surface area and age.